Huntington disease iPSCs show early molecular changes in intracellular signaling, the expression of oxidative stress proteins and the p53 pathway - Wojciech J. Szlachcic; Pawel M. Switonski; Wlodzimierz J. Krzyzosiak; Marek Figlerowicz; Maciej Figiel (The Company of Biologists, 2015)
Huntington disease (HD) is a brain disorder characterized by the late onset of motor and cognitive symptoms, even though the neurons in the brain begin to suffer dysfunction and degeneration long before symptoms appear. There is currently no cure. Several molecular and developmental effects of HD have been identified using neural stem cells (NSCs) and differentiated cells, such as neurons and astrocytes. Still, little is known regarding the molecular pathogenesis of HD in pluripotent cells, such as embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs). Therefore, we examined putative signaling pathways and processes involved in HD pathogenesis in pluripotent cells. We tested naïve mouse HD YAC128 iPSCs and two types of human HD iPSC that were generated from HD and juvenile-HD patients. Surprisingly, we found that a number of changes affecting cellular processes in HD were also present in undifferentiated pluripotent HD iPSCs, including the dysregulation of the MAPK and Wnt signaling pathways and the dysregulation of the expression of genes related to oxidative stress, such as Sod1. Interestingly, a common protein interactor of the huntingtin protein and the proteins in the above pathways is p53, and the expression of p53 was dysregulated in HD YAC128 iPSCs and human HD iPSCs. In summary, our findings demonstrate that multiple molecular pathways that are characteristically dysregulated in HD are already altered in undifferentiated pluripotent cells and that the pathogenesis of HD might begin during the early stages of life.